Dynamic Algorithms for the Dyck Languages - Frandsen, Gudmund Skovbjerg; Husfeldt, Thore; Miltersen, Peter Bro; Rauhe, Theis; Skyum, Søren (BRICS Report Series, 1995)
We study dynamic membership problems for the Dyck languages, the class of strings of properly balanced parentheses. We also study the Dynamic Word problem for the free group. We present deterministic algorithms and data structures which maintain a string under replacements of symbols, insertions, and deletions of symbols, and language membership queries. Updates and queries are handled in polylogarithmic time. We also give both Las Vegas- and Monte Carlo-type randomised algorithms to achieve better running times, and present lower bounds on the complexity for variants of the problems.